2015
DOI: 10.1080/19420862.2015.1007810
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for antagonistic activity of anifrolumab, an anti-interferon–α receptor 1 antibody

Abstract: Anifrolumab (anifrolumab) is an antagonist human monoclonal antibody that targets interferon a receptor 1 (IFNAR1). Anifrolumab has been developed to treat autoimmune diseases and is currently in clinical trials. To decipher the molecular basis of its mechanism of action, we engaged in multiple epitope mapping approaches to determine how it interacts with IFNAR1 and antagonizes the receptor. We identified the epitope of anifrolumab using enzymatic fragmentation, phage-peptide library panning and mutagenesis ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 43 publications
3
82
0
8
Order By: Relevance
“…Anifrolumab, a human monoclonal antibody against the interferon α receptor 1(56), is currently being studied as a potential new therapy for lupus. A phase II open label trial in 17 Japanese patients with SLE showed that anifrolumab suppressed interferon gene signatures in 85% of patients at the 300 mg dose at day 169 and 95% of patients in the 1000 mg dose at day 85 without any safety signals(57).…”
Section: Introductionmentioning
confidence: 99%
“…Anifrolumab, a human monoclonal antibody against the interferon α receptor 1(56), is currently being studied as a potential new therapy for lupus. A phase II open label trial in 17 Japanese patients with SLE showed that anifrolumab suppressed interferon gene signatures in 85% of patients at the 300 mg dose at day 169 and 95% of patients in the 1000 mg dose at day 85 without any safety signals(57).…”
Section: Introductionmentioning
confidence: 99%
“…20 Several teams have also used peptide-based technologies to identify antibody epitope and even model antibody-target complex. 6,21 Nevertheless, despite being very well adapted to linear epitope, this approach was not suitable for the study of Hu 15C1 as its epitope is conformational. Several studies have also used computational protein docking in order to predict antibody epitope and paratope before experimental validation by site directed mutagenesis, 22 but these approaches do not provide information of potential amino acids contacts at the interface between the antibody and its target.…”
Section: Discussionmentioning
confidence: 97%
“…There are 2 potential explanations for this. The anti‐IFNAR monoclonal antibody might compete with IFNα2 for binding to IFNAR‐1, as is true of other anti–IFNAR‐1 monoclonal antibodies . Alternatively, since type I IFN binding induces IFNAR‐1 internalization , receptor expression could be modulated by endogenous type I IFN (SLE patients) or exogenous IFNα2b (in vitro).…”
Section: Discussionmentioning
confidence: 99%